Digital Panoramic Radiography for Forensic Dental Age Estimation: A Biostatistical Validation Demonstrating the Superiority of the Willems Method over the Cameriere Approach in a Pediatric Cohort (6–14 Years) - Asep Darya Darma Putra; Rahmatul Aini; Safitra Ade Erman (HM Publisher, 2026)
Background: Accurate dental age (DA) estimation is critical in pediatric dentistry, orthodontics, and forensic identification. Radiomorphological and radiometric techniques are widely utilized, yet their accuracy varies across diverse ethnic populations. This study aims to evaluate and compare the accuracy of the Willems (radiomorphological) and Cameriere (radiometric) methods against chronological age (CA) in a pediatric population in Padang, Indonesia. Methods: A retrospective cross-sectional study was conducted using 168 digital panoramic radiographs of children (96 males, 72 females) aged 6 to 14 years. Dental maturation was assessed digitally utilizing CorelDraw X7. The Willems method evaluated the developmental stages of seven left mandibular teeth, while the Cameriere method measured open apices. Statistical analysis included paired t-tests, Pearson correlation coefficients, Mean Absolute Error (MAE), and Root Mean Square Error (RMSE) to rigorously assess accuracy. Results: The mean CA of the cohort was 9.91 ± 0.28 years. The Cameriere method consistently underestimated DA across all age cohorts, yielding a mean DA of 8.63 ± 0.93 years (p < 0.05). Conversely, the Willems method demonstrated a mean DA of 10.73 ± 1.06 years, showing higher overall concordance with CA without statistically significant broad-scale deviations in the overarching comparative model (p < 0.05), despite minor stage-specific variances. Both methods exhibited a near-perfect positive correlation with CA (r > 0.98). Conclusion: The Willems radiomorphological method significantly outperforms the radiometric Cameriere approach in this specific Southeast Asian pediatric demographic. The Cameriere method requires population-specific formulaic adaptation due to consistent physiological underestimation.